Evaluasi Daya Gabung, Heterosis, dan Heterobeltiosis Hasil Persilangan Half Diallel Capsicum annuum L. - Undang Undang; Wahyu Trimulyono Safudin; Arifah Rahayu; Setyono Setyono (Universitas Gadjah Mada, 2026)
Low chili yields in Indonesia are triggered by poor seed quality, inefficient cultivation practices, and high levels of pest and disease attacks. As a solution, plant breeding programs are implemented to improve the quality of genetic traits. This study aims to evaluate GCA, SCA, and heterosis and heterobeltiosis values from half-diallel crosses involving five chili parents. Using a one-factor RCBD, this study tested 15 genotypes (5 parents and 10 hybrids) with three replications. The analysis results showed significant differences in GCA and SCA values across all parameters. Genotype F7.110005 showed the best DGU value in almost all vegetative and generative characters observed, Ungara was superior in fruit diameter (1,92), fruit flesh thickness (0,25) and number of seeds (7,52), Viola in flowering age (-4,10) and harvest age (-3,97) earlier, F12.145291 in number of fruits (32,41), Adelina in leaf width (0,24). The Ungara x Adelina hybrid had the highest frequency of positive values in the parameters of DGK, heterosis, and heterobeltiosis. Meanwhile, the F7.110005 x Adelina hybrid had the highest DGK value in the leaf length character (0,92), although it had some negative heterosis values. Both of these cross combinations are recommended for the development of superior hybrid varieties.